Central Precocious Puberty as a Sign of Congenital Adrenal Hyperplasia: Case Presentations - Markosyan, R.L.; Navasardyan, L.V. (International Journal of Child Health and Nutrition, 2020)
Central precocious puberty results from the premature activation of the hypothalamic-pituitary-gonadal axis. Rarely congenital adrenal hyperplasia and/or its inappropriate treatment can be a peripheral cause of CPP. There are very few case reports of this etiology. Chronic mildly to moderately elevated adrenal androgens or intermittent hyperandrogenemia in congenital adrenal hyperplasia may trigger the precocious activation of the hypothalamic-pituitary axis, leading to CPP. In the current work, we describe 6 cases of late diagnosis of congenital adrenal hyperplasia associated with central precocious puberty. Central precocious puberty seems to be a complication of congenital adrenal hyperplasia, particularly in countries where a routine neonatal screening program for this condition is lacking. It is unclear whether these patients could avoid central precocious puberty development if the congenital adrenal hyperplasia was diagnosed in the neonatal period and appropriately treated. The current work underlines the need for congenital adrenal hyperplasia neonatal screening implementation and further investigation of the association of these two endocrine disorders